2022
DOI: 10.1101/2022.02.09.479588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic Memory of COVID-19 in Innate Immune Cells and Their Progenitors

Abstract: Severe coronavirus disease 2019 (COVID-19) is characterized by systemic inflammation and can result in protracted symptoms. Robust systemic inflammation may trigger persistent changes in hematopoietic cells and innate immune memory through epigenetic mechanisms. We reveal that rare circulating hematopoietic stem and progenitor cells (HSPC), enriched from human blood, match the diversity of HSPC in bone marrow, enabling investigation of hematopoiesis and HSPC epigenomics. Following COVID-19, HSPC retain epigeno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 114 publications
(114 reference statements)
0
33
1
Order By: Relevance
“…Overall, we identified marked alterations to the expression of surface markers across myeloid cell types following COVID-19, which could play a part in the resulting immune suppression. The long-term changes to the surface expression of these proteins on monocytes and DC may be due to ongoing inflammation or epigenetic changes resulting from severe COVID-19 ( 77 ), possibly altering progenitors in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we identified marked alterations to the expression of surface markers across myeloid cell types following COVID-19, which could play a part in the resulting immune suppression. The long-term changes to the surface expression of these proteins on monocytes and DC may be due to ongoing inflammation or epigenetic changes resulting from severe COVID-19 ( 77 ), possibly altering progenitors in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we identified marked alterations to the expression of surface markers across myeloid cell types following COVID-19. The long-term changes to the surface expression of these proteins on monocytes and DC may be due to epigenetic changes resulting from severe COVID-19 79 , possibly altering progenitors in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we identified marked alterations to the expression of surface markers across myeloid cell types following COVID-19. The long-term changes to the surface expression of these proteins on monocytes and DC may be due to epigenetic changes resulting from severe COVID-19 79 , possibly altering progenitors in the bone marrow. COVID-19 severity has been linked to an array of clinical parameters such as the level of soluble urokinase plasminogen activator receptor (suPAR), CRP, and viral load [80][81][82][83] .…”
Section: Discussionmentioning
confidence: 99%
“…Four to 12 months after COVID-19 infection, single-cell transcriptomic and epigenomic analysis of the peripheral blood mononuclear cells enriched in CD34 + HSPCs of affected individuals revealed that that progenitor cells retain their granulopoiesis bias. 141 Specifically, HSPCs from COVID-19-recovered patients demonstrate higher expression of S100A8/A9 and CSF3R and increased chromatin accessibility of these loci. Moreover, mature monocytes retain the altered chromatin accessibility found in progenitor cells and present an increased Type I IFN signature.…”
Section: Neutrophil S and G R Anulop Oie S Is In Tr Ained Innate Immu...mentioning
confidence: 95%